1974
DOI: 10.1073/pnas.71.12.4955
|View full text |Cite
|
Sign up to set email alerts
|

Unscheduled DNA Synthesis in the Germ Cells of Male Mice Exposed In Vivo to the Chemical Mutagen Ethyl Methanesulfonate

Abstract: An unscheduled DNA synthesis has been clearly demonstrated in meiotic and postmeiotic germ cell stages of the male mouse after in vivo treatment with a 250 mg/kg dose of ethyl methanesulfonate. The germ cell stages showing unscheduled DNA synthesis range from early to middle meiotic prophase stages through early to middle spermatid stages. The initiation of this synthesis, taken to be repair of chemically damaged DNA in these germ cells, is rapid, beginning within 1 hour after the injection of ethyl methanesul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(40 citation statements)
references
References 22 publications
7
33
0
Order By: Relevance
“…Our results confirm and extend prior studies of the DNA repair-deficient window during spermiogenesis [13][14][15][16][17][18][19][20]. The results of our experiments showed that the frequencies of zygotes with chromosomal aberrations were significantly higher when a total dose of 28 mg/kg DEB was given over days 14 through 8 before mating than when it was given as a single dose 14 days before mating (Table 2 and Figure 3A).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results confirm and extend prior studies of the DNA repair-deficient window during spermiogenesis [13][14][15][16][17][18][19][20]. The results of our experiments showed that the frequencies of zygotes with chromosomal aberrations were significantly higher when a total dose of 28 mg/kg DEB was given over days 14 through 8 before mating than when it was given as a single dose 14 days before mating (Table 2 and Figure 3A).…”
Section: Discussionsupporting
confidence: 82%
“…These results show that the last two weeks of mouse spermiogenesis, which corresponds to the period of spermatogenesis that is thought to be DNA repair-deficient in prior studies [13][14][15][16][17][18][19][20], is also the sensitive window for induction of chromosomal aberrations in sperm after paternal exposure to DEB, and that both sperm and late spermatids are unable to repair DEB-induced damage.…”
Section: Chromosomal Aberrations Detected In Zygotes After Repeated Ementioning
confidence: 82%
See 1 more Smart Citation
“…Further studieds are required to determine whether DNA repair plays a significant role in the modification of genetic damage in postcopulation-precleavage germ cells and zygotes as well as in spermatogenesis (Generoso et al 1979;Sega 1974;Tanaka and Katoh 1979 …”
Section: Discussionmentioning
confidence: 99%
“…Kof man-Alf aro and Chandley (1971) reported the detection of UDS in germ cell cultures in vitro after UV and X-ray treatment, and Beikrich (1977) demonstrated UDS induced by chemicals. Sega et al (Sega 1974;Sega et al 1976;Sega 1976;Sega et al 1978), on the other hand, described the measurement of UDS in the germ cells of mice treated with X-rays and chemicals, and proposed the use of this procedure as a mammalian screening test system for the detection of mutagens.…”
Section: Introductionmentioning
confidence: 99%